[Spanish translation] Planning the teaching of handball on the basis of defensive organization: application in school physical education, sports initiation and college sports - Pombo Menezes, Rafael (2024)
Planning activities in group sports is an inherent task for teachers and coaches, directly influenced by the context of the team and by the training of the professionals involved. The aim of this article is to present the structure of the Teaching Model of Invasion Games based on Defensive Organization (MEJIOD) and to propose its application in different contexts (school, extra-curricular sports initiation –under 10, under 12 and under 14– and college students). MEJIOD is supported by three pillars: game model, flexible tactical behavior and principles of contemporary teaching models. The progression proposal for teaching handball starts with unorganized defenses and moves towards individual and zonal defenses, which supports the planning proposals in the aforementioned contexts, considering the experience of players and the gradual increase in the complexity of the game. The expectation is to present potential guidelines to back up the work of teachers and coaches in these contexts and to amplify the reflection on this topic.